Critical reading in the content areas 04/05 : (McGraw-Hill/Duskin, 2005)
Critical Reading in the Content Areas is a collection of articles from the best of the public press. The articles discuss perspectives on teaching literacy; collaborative learning; reading strategies; simplification of textbooks; textbook comprehension; and questioning strategies. Adopters have access to Dushkin Online, a student website designed to support Annual Editions titles.